Physical laboratory at the center of the Galaxy. (9th November 2015) - Dokuchaev, V I; Eroshenko, Yu N
Abstract: We review the physical processes that occur at the center of the Galaxy and that are related to the supermassive black hole SgrA* residing there. The discovery of high-velocity S0 stars orbiting SgrA* for the first time allowed measuring the mass of this supermassive black hole, the closest one to us, with a 10% accuracy, with the result M_h=(4.1±0.4)×10^6M_ . Further monitoring can potentially discover the Newtonian precession of the S0 star orbits in the gravitational field of the black hole due to invisible distributed matter. This will yield the `weight' of the elusive dark matter concentrated there and provide new information for the identification of dark matter particles. The weak accretion activity of the `dormant quasar' at the galactic center occasionally shows up as quasiperiodic X-ray and near-IR oscillations with mean periods of 11 and 19 min. These oscillations can possibly be interpreted as related to the rotation frequency of the SgrA* event horizon and to the latitude oscillations of hot plasma spots in the accretion disk. Both these frequencies depend only on the black hole gravitational field and not on the accretion model. Using this interpretation yields quite accurate values for both the mass M_h and the spin a (Kerr rotation parameter) of SgrA*: M_h= (4.2±0.2) ×10^6M_ and a=0.65±0.05 .